Banking Union’s impact on financial stability – holistic approach - Zielińska-Lont, Klaudia (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
Prudential supervision of credit institutions in the European Union has for a long time been the responsibility of national bodies, even though this did not match the international character of the activities of many supervised banks. After the establishment of the banking union’s Single Supervisory Mechanism this has changed particularly for systemically important credit institutions, that now fall under the direct, coordinated supervision under the auspice of the European Central Bank. There was a great deal of speculation around what changes the banking union would bring to the financial sector in Europe, yet the net impact of the Single Supervisory Mechanism on financial stability and competitive position of the supervised credit institutions remains largely unknown. This monograph presents a holistic analysis of the impact that the reform of the EU’s financial safety net had on the banking sector. To make such evaluation possible, a dedicated synthetic indicator was designed to quantify the net impact of harmonized prudential supervision on the stability of credit institutions. The results signal that the establishment of the Single Supervisory Mechanism was a success and that the proposed synthetic indicator can serve as an early warning tool for authorities tasked with safeguarding financial stability.